The incidence of stunting, the frequency/duration of diarrhea and Acute Respiratory Infection in toddlers - Diyah Arini; Nursalam; Mahmudah; Ike Faradilah (SAGE Publishing, 2020)
Background: Infectious diseases such as diarrhea and Acute Respiratory Infection (ARI) lead to loss of appetite in children and stunting growth. This study analyzes the relationship between the incidence of stunting and the frequency/duration of diarrhea and ARI in children under five years. Design and Methods: The stratified random sampling method was used to obtain data from 152 children in 4 villages in Surabaya, East Java, Indonesia. Results: The results showed that children under the age of five, experience higher stunting duration and longer frequency of diarrhea. The Rho Spearmen Test showed differences in the incidence of stunting with the frequency of diarrhea P = 0.005 (P<α = 0.05), P = 0.003 (P<α = 0.05), with ARI of P =0.001 (P<α = 0.05). Conclusions: In conclusion, stunting is related to the frequency and duration of diarrheal diseases and ARI, therefore, community- integrated health center need to carryout counseling activities on children less than five years to determine their health status.